Program ODOPOS ( One Day One Problem One Solution) In Realistic Mathematics-Based Online - Diah Sulistiyowati; Nur Fauziyah; Fatimatul Khikmiyah (Universitas Muhammadiyah Gresik, 2020)
ABSTRAK The purpose of this research is to develop ODOPOS (one day one problem one solution) program in realistic mathematic that is based online. By application of realistic mathematics is expected to have students the ability to understand mathematics in real life. The sample of this study is 33 students at V grade of Elementary School of Muhammadiyah Manyar at 2019-2020 academic years. The research instrument is a pretest-posttest test and student response questionnaire sheet. Result of the study: (1) Development of ODOPOS (one day one problem one solution) program in realistic mathematic based online is: (a) Analyze stage, includes analysis of student characteristics and material analysis (b) Design stage, there is a use case diagram that is: home, profile, log in, summary and examples of problems, exercises, scores and class progress (c) Development stage is developing the ODOPOS program design based on the use case diagram. (d) Implementation stage, is the result of the development ODOPOS program being applied in learning for one week (e) evaluation stage, is giving a pretest-posttest test and student questionnaire response sheet (2) there is an increase in student achievement 84 , 84%. The students get an n-gain score of 0.7 for the high category from the use of the ODOPOS (one day one problem one solution) program. (3) Students responses to the ODOPOS program, based on the content criteria, the result is 93.49% or very feasible